2006
DOI: 10.1089/acm.2006.12.281
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Complementary and Alternative Medicine (CAM) Use Across Racial/Ethnic Groups and the Development of Ethnic-Specific Measures of CAM Use

Abstract: Patterns of CAM use and ethnic-specific CAM use vary across racial/ethnic groups. Evaluation of CAM use in ethnically diverse populations should recognize ethnic-specific modalities and variation across ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
80
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 21 publications
12
80
2
Order By: Relevance
“…[71][72][73] For example, population studies suggest that the ethnic groups that are low users of conventional supportive group interventions may be relatively high users of CAM. 25,28 As the fields of cancer survivorship and health disparities grow, it will be important to access hardto-reach and underserved populations. Therefore, we need to continue exploring novel interventions and options for support for the growing and diverse population of cancer survivors.…”
Section: Psychosocial Stress and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[71][72][73] For example, population studies suggest that the ethnic groups that are low users of conventional supportive group interventions may be relatively high users of CAM. 25,28 As the fields of cancer survivorship and health disparities grow, it will be important to access hardto-reach and underserved populations. Therefore, we need to continue exploring novel interventions and options for support for the growing and diverse population of cancer survivors.…”
Section: Psychosocial Stress and Cancermentioning
confidence: 99%
“…27 Although, at this point, there has been little formal assessment of patterns and predictors of CAM use among cancer survivors from diverse ethnic groups, some data suggest that CAM use is overall similarly high across ethnic groups, with subgroup variations in patterns of use. 25,28 For example, although use of mind-body therapies is consistently high on the list of commonly used CAM modalities overall, it is particularly high in some minority subgroups such as African Americans. 25 There are potential advantages for practitioners to be able to discuss CAM with their patients and, in some cases, to integrate it with conventional care.…”
mentioning
confidence: 99%
“…7 A limitation of most studies' designs was that patient surveys were available in only English. 8 When multilanguage surveys or interpreters were accessible, a study showed an even higher percentage of Hispanic CAM users (63%). 9 Variation in results may also be attributed to different definitions of CAM across studies.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] In one study, for example, Barnes et al 10 demonstrated that 43.1% of white adults sought out CAM treatments in comparison to 25.5% of blacks. Furthermore, there is minimal research that provides an explanation as to why blacks use CAM less often.…”
Section: Introductionmentioning
confidence: 99%
“…25 All existing survey research studies demonstrate that blacks use chiropractic health care services less often than whites. [2][3][4][5][6][7]9,15,16,[26][27][28][29] In many instances, whites used chiropractic at least twice as often as blacks. 2,4,6,7,9,15,16,26,29 Some have attributed this difference to the perception of discrepancies of health care treatment by blacks, lower average educational levels of blacks compared to whites, and the lack of accessibility to doctors of chiropractic (DCs) in black communities.…”
Section: Introductionmentioning
confidence: 99%